2008
DOI: 10.1038/eye.2008.354
|View full text |Cite
|
Sign up to set email alerts
|

Can a preoperative bevacizumab injection prevent recurrent postvitrectomy diabetic vitreous haemorrhage?

Abstract: Aims To evaluate the recurrence rate of vitreous haemorrhage (VH) in patients treated with one intravitreal bevacizumab (IVB) injection (2.5 mg/0.1 ml) before planned pars plana vitrectomy for treatment of diabetic nonclearing VH. Methods Prospective pilot study of 32 eyes of 31 consecutive diabetic patients who underwent IVB injection within 1 week before surgery for persistent VH in the presence of active proliferative diabetic retinopathy. Three masked retinal specialists graded the amount of VH from grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 11 publications
0
27
0
3
Order By: Relevance
“…Regarding recurrent VH; although we did not see a significant difference between the IVB and non-IVB groups, others have reported that preoperative IVB did lower the incidence of postoperative VH. 7,9,[12][13][14] The main limitation of our study was the selection of patients for preoperative IVB. Initially, in 2006, when we started using this adjunct for PPV, there was a selection bias for using IVB in eyes with more vascular membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding recurrent VH; although we did not see a significant difference between the IVB and non-IVB groups, others have reported that preoperative IVB did lower the incidence of postoperative VH. 7,9,[12][13][14] The main limitation of our study was the selection of patients for preoperative IVB. Initially, in 2006, when we started using this adjunct for PPV, there was a selection bias for using IVB in eyes with more vascular membranes.…”
Section: Discussionmentioning
confidence: 99%
“…This vascular endothelial growth factor inhibitor has been reported to decrease intraoperative hemorrhage and facilitate fibrovascular membrane dissection, [3][4][5][6][7][8][9][10][11][12] and reduce postoperative vitreous hemorrhage (VH) rates. 9,[12][13][14] However, these studies were limited by relatively small numbers, heterogeneous retinal pathology (TRD and VH were studied together), and varying surgical techniques (multiple surgeons and multiple gauge vitrectomies). Concern still exists that IVB may worsen TRD, 6,[15][16][17] and may cause the foveal vascular zone enlargement.…”
Section: Introductionmentioning
confidence: 99%
“…The preoperative injection of intravitreal bevacizumab may reduce intraoperative bleeding during dissection of membrane in PDR with tractional retinal detachment (17) . Intravitreal bevacizumab injection may not prevent postoperative VH, probably due to washing of bevacizumab during vitrectomy (20) . In this study, immediate postoperative VH occurred in 1 eyes in group 1, 4 eyes in group 2 and 8 eyes of the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a pilot study of bevacizumab injected immediately after vitrectomy for vitreous hemorrhage was conducted (32) . In these studies, the bevacizumab dose ranged from 1 to 2.5 mg and the time of drug administration before surgery ranged from 1 to 30 days, with the patients usually being operated about 7 days after the intravitreal injection (18)(19)(20)22,(26)(27)(28)(29) . This time is considered to be safe in order to avoid complications of increased fibrosis and vitreoretinal traction, with regression of active neovessels and reduction of high VEGF levels characteristic of PDR having been observed (33) .…”
Section: Preoperative Administration Of Anti-vegf Drugs Before Pars Pmentioning
confidence: 99%
“…Bevacizumab has been used preoperatively as an adjuvant in vitrectomy in patients with TRD, vitreal hemorrhage, mixed TRD, active fibrovascular proliferation (FVP) (3,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) , and neovascular glaucoma (31) (Table 1). Also, a pilot study of bevacizumab injected immediately after vitrectomy for vitreous hemorrhage was conducted (32) .…”
Section: Preoperative Administration Of Anti-vegf Drugs Before Pars Pmentioning
confidence: 99%